PENGARUH KONSENTRASI PACLOBUTRAZOL DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicon esculentum) - Nella Oktavianty Sugiharto; Agus Sulistyono; Nora Augustien Kusumaningrum (Plumula : Berkala Ilmiah Agroteknologi, 2022)
Tomato is a type of horticultural commodity that is quite in demand by the people of Indonesia because of its high nutritional content. The aims of this research is to determine the effect of paclobutrazol concentration and dose of NPK fertilizer on the growth and yield of tomato plants. This research was conducted on the experimental garden of the Faculty of Agriculture, University of National Development "Veteran" East Java in December 2020 - March 2020 using polybags. This research is a factorial experiment based on a Randomized Complete Block Design (RCBD) consisting of two factors, the first factor is the concentration of paclobutrazol (P) consisting of: P0 = 0 ppm (control), P1 = 150 ppm, P2 = 300 ppm, P3 = 450 ppm and the second factor is dose of NPK fertilizer consisted of: N0 = 25 g/plant (control), N1 = 12,5 g/plant, N2 = 20 g/plant, N3 = 27,5 g/plant. The results showed that the combination of 150 ppm paclobutrazol + 27,5 g/plant of NPK fertilizer increased the number of flowers, total number of fruits, fruit weight per fruit, fruitset, and Vitamin C content.